(untitled) (Journal of the College of Basic Education, 2022)
The image of the universe - the mandala (Mandala) appeared on a number of Buddhist works of art such as architecture, sculpture and drawing, and although the image of the universe in Indian thought needs more research and study, the aim of this topic is to know the general idea of the hypothetical image of the universe in Buddhist thought through a review And analyze some of the works of art that have reached us.